2006
DOI: 10.1055/s-2006-944617
|View full text |Cite
|
Sign up to set email alerts
|

Two-stage treatment with preoperative endoscopic retrograde cholangiopancreatography (ERCP) compared with single-stage treatment with intraoperative ERCP for patients with symptomatic cholelithiasis with possible choledocholithiasis

Abstract: Both treatment approaches were equally effective but the intraoperative ERCP group had less morbidity, a shorter hospital stay, and reduced costs. The lower morbidity in the intraoperative ERCP group resulted from the lower rate of papillotomy and lower rates of post-ERCP pancreatitis and cholecystitis. Total morbidity was principally related to the type of treatment approach used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
113
0
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(125 citation statements)
references
References 14 publications
3
113
0
5
Order By: Relevance
“…The length of hospital stay (8 [SD 5] days v. 5 [SD 3] days, p < 0.001) and costs were lower in the intraoperative ERCP group, but the operative times were longer. 30 Similar results were obtained in a randomized trial involving patients whose stones were diagnosed by means of magnetic reso- Elevated bilirubin level; advanced; or evidence of stones in the common bile duct on ultrasound or computed tomography images…”
Section: Pre-or Postoperative Ercp Versus Laparoscopic Cholecystectomysupporting
confidence: 61%
“…The length of hospital stay (8 [SD 5] days v. 5 [SD 3] days, p < 0.001) and costs were lower in the intraoperative ERCP group, but the operative times were longer. 30 Similar results were obtained in a randomized trial involving patients whose stones were diagnosed by means of magnetic reso- Elevated bilirubin level; advanced; or evidence of stones in the common bile duct on ultrasound or computed tomography images…”
Section: Pre-or Postoperative Ercp Versus Laparoscopic Cholecystectomysupporting
confidence: 61%
“…comparative study of 200 patients, suggesting the superiority of RVT over preoperative ERCP in terms of hospital stay. In contrast, the RCT published by Rábago et al [86] reported similar percentages of CBD clearance between the two approaches. A study by Hong et al [87] compared LCDE and RVT, and no differences were found between the two groups regarding duration of surgery, success rate, complications, retained stones, hospital stay, and costs.…”
Section: Comparing the Different Techniquesmentioning
confidence: 76%
“…The published papers describing patients treated with a single-stage laparoendoscopic treatment of gallstones and CBD stones are shown in Table 1 [7,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. The data were collected from 20 original papers reporting studies involving 8 [11] to 93 [26] patients.…”
Section: Resultsmentioning
confidence: 99%